2003
DOI: 10.1021/cm034443o
|View full text |Cite
|
Sign up to set email alerts
|

Application of De-silylation Strategies to the Preparation of Transition Metal Pnictide Nanocrystals:  The Case of FeP

Abstract: Phase-pure FeP nanoparticles have been synthesized by the reaction of iron(III) acetylacetonate with tris(trimethylsilyl)phosphine at temperatures of 240-320 °C using trioctylphosphine oxide as a solvent and dodecylamine (DA), myristic acid (MA), or hexylphosphonic acid (HPA) as additional capping groups (ligands). The DA-capped particles prepared at 260 °C have an average diameter of 4.65 ( 0.74 nm with FeP being the only observed crystalline phase. Elemental analyses indicate a high percentage yield of FeP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 28 publications
(42 reference statements)
7
55
0
Order By: Relevance
“…[24] We soon found that co-surfactants such as dodecylamine (DA) or myristic acid (MA) are essential to moderate the reactivity, thus resulting in a high yield (85 % based on iron consumption) of soluble colloid. [25] Consistent with our assumptions about redox-neutral reactions, the powder X-ray diffraction (PXRD) pattern revealed that the likely product was nanocrystalline FeP (Figure 1 a). Furthermore, transmission electron microscopy (TEM) indicated that, in contrast to the solvothermal method, discrete spherical nanoparticles (ca.…”
Section: Unsupported Transition-metal Phosphide Nanoparticlessupporting
confidence: 80%
See 2 more Smart Citations
“…[24] We soon found that co-surfactants such as dodecylamine (DA) or myristic acid (MA) are essential to moderate the reactivity, thus resulting in a high yield (85 % based on iron consumption) of soluble colloid. [25] Consistent with our assumptions about redox-neutral reactions, the powder X-ray diffraction (PXRD) pattern revealed that the likely product was nanocrystalline FeP (Figure 1 a). Furthermore, transmission electron microscopy (TEM) indicated that, in contrast to the solvothermal method, discrete spherical nanoparticles (ca.…”
Section: Unsupported Transition-metal Phosphide Nanoparticlessupporting
confidence: 80%
“…From magnetic susceptibility measurements on nanocrystalline FeP and MnP, we find that in both cases the transition to a helimagnetic state is completely shut down in the nanoparticles. [25,26] We attribute this to the fact that the nanoparticle dimension (4±8 nm) is approaching that of the magnetic unit cell for the helimagnetic configuration, thereby destabilizing this state. The consequence is that nanoparticulate FeP appears to be paramagnetic over the entire temperature range studied (300±5 K, Figure 3), whereas nanoparticulate MnP is ferromagnetic at all temperatures less than T c (Figure 4).…”
Section: Magnetic Properties Of Fep and Mnpmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Typical methods used to synthesize high-quality colloidal Ni 2 P nanocrystals use traditional organic solvents (e.g., octadecene (ODE), dioctyl ether), expensive and/or reactive phosphide precursors (tri-n-octylphosphine (TOP), white phosphorus (P 4 ), tris(trimethylsilyl)phosphine (P(TMS) 3 ), and tri-n-butylphosphine), high temperatures, and/or multiple-step reactions. 10,[15][16][17] Triphenylphosphine (PPh 3 ) is a low-cost, less-reactive, and more air-stable phosphide precursor (~15% the cost of TOP in price per mole); 18 however, compared to TOP and P(TMS) 3 , nanocrystals synthesized using PPh 3 are typically large (>45 nm), ill-defined, amorphous, and/or not phase pure. [18][19][20] Herein, we report the one-step, heating up synthesis of Ni 2 P nanocrystals using Ni(acac) 2 , PPh 3 , oleylamine (OAm), and 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (BMIM-Tf 2 N) as the IL solvent (Eq.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Similarly, ternary metal phosphides in bulk such as Fe 2Àx Mn x P, [12] Fe 2Àx Co x P, [13] Co 1Àx Mn x P, [14] and Ni 2Àx Mo x P [15] have been extensively studied as well; in contrast, their corresponding ternary transition-metal phosphide nanostructures (e.g., M 1Àx M' x P or M 2Àx M' x P) have been rarely explored so far. In comparison, ternary transition-metal oxide or chalcogenide nanostructures like Mg x Zn 1Àx O, Zn x Cd 1Àx S, and Zn x Cd 1Àx Se nanocrystals (e.g., dots, rods, or tetrapods) have been recently prepared and have been shown to exhibit tunable properties by changing their compositions and structures.…”
Section: Introductionmentioning
confidence: 99%